Genetic Screening of the Usher Syndrome in Cuba - Santana, Elayne E.; Fuster-García, Carla; Aller, Elena; Jaijo, Teresa; García-Bohórquez, Belén; García-García, Gema; Millán, José M.; Lantigua, Araceli (Frontiers in Genetics, 2019)
Background: Usher syndrome (USH) is a recessive inherited disease characterized by sensorineural hearing loss, retinitis pigmentosa and, sometimes, vestibular dysfunction. Although the molecular epidemiology of Usher syndrome has been well studied in Europe and The United States of America, there is a lack of studies in other regions like Africa or Central and South America. Methods: We designed a NGS panel that included the 10 USH causative genes (MYO7A, USH1C, CDH23, PCDH15, USH1G, CIB2, USH2A, ADGRV1, WHRN and CLRN1), four USH associated genes (HARS, PDZD7, CEP250 and C2orf71), and the region comprising the deep-intronic c.7595-2144A>G mutation in USH2A. Results: NGS sequencing was performed in 11 USH patients from Cuba. All the cases were solved. We found the responsible mutations in the USH2A, ADGRV1, CDH23, PCDH15 and CLRN1 genes. Four mutations have not been previously reported. Two mutations are recurrent in this study: c.619C>T (p.Arg207*) in CLRN1, previously reported in two unrelated Spanish families of Basque origin, and c.4488G>C (p.Gln1496His) in CDH23, first described in a large Cuban family. Additionally, c.4488G>C has been reported two more times in the literature in two unrelated families of Spanish origin. Conclusions: Although the sample size is very small, it is tempting to speculate that the gene frequencies in Cuba are distinct from other populations mainly due to an “island effect” and genetic drift. The two recurrent mutations appear to be of Spanish origin. Further studies with a larger cohort are needed to elucidate the real genetic landscape of Usher syndrome in the Cuban population.